Depiction of Culture in The Film Tenggelamnya Kapal Van Der Wijck - Puti Andam Dewi; Joko Aswoyo; Eggy Triana Putri (Capture : Jurnal Seni Media Rekam, 2023)
This study aims to examine cultural values portrayed through the mise en scène in the film. One film explored for its cultural background is ‘Tenggelamnya Kapal Van Der Wijck', which showcases Minangkabau culture. This film is adapted from Buya Hamka's novel of the same title. The mise en scène elements played an important role in shaping the audience's understanding of the story, which was conveyed through the use of cultural elements such as houses, everyday clothes, and property. This study used a qualitative method of media text analysis and utilized a purposive sampling technique. The results show a distinct clothing gap between characters, indicating disparities within the Minang community, including the disadvantaged or lower middle class. This critique highlights the overlap in the depiction of Minangkabau culture in the film ‘Tenggelamnya Kapal Van Der Wijck’, examining it through the lens of mise-en-scène. Keywords: culture, film, Tenggelamnya Kapal Van Der Wijck